Alterations of lipoprotein subfractions in GH-deficient adults - Ratku, Balázs; Lőrincz, Hajnalka; Csiha, Sára; Bíró, Lajos; Erdei, Annamária; Berta, Eszter; Ujvárosy, Dóra; Bodor, Miklós; Nagy, Endre V.; Szabó, Zoltán; Harangi, Mariann; Somodi, Sándor (Frontiers in Endocrinology, 2025)
IntroductionDyslipidemia is a common complication of adult growth hormone deficiency (AGHD) and considered an important contributor to increased mortality. Previous studies mainly focused on quantitative assessment of lipoproteins, but lipoprotein subfractions and their relationship with insulin-like growth factor 1 (IGF-1) have not been explored.PurposeTo perform a comprehensive evaluation of lipoprotein subfractions and measuring apolipoprotein L1 (apoL1), sphingosine 1-phosphate (S1P) and apolipoprotein M (apoM) in AGHD.Materials and methods11 GH-substituted (GHS) patients, 9 GH-unsubstituted (GHU) patients and 37 controls were included in the study. Lipoprotein subfractions were separated by the Lipoprint system. ApoL1, apoM and S1P were determined by ELISA. In the GHS patients GH-replacement was discontinued for 2 months. Measurements were performed before GH-discontinuation, at the end of the 2-month GH-withdrawal, and 1 month after reinstituting GH-replacement.ResultsStandard lipid parameters, apoM and apoL levels were not different between the groups. GHU patients demonstrated lower apolipoprotein A1 compared to controls (p=0.02) and higher apolipoprotein B100 compared to GHS (p=0.02). GHU and GHS showed higher S1P levels compared to controls (p=0.04 and p=0.01, respectively). Both GHU and GHS patients also presented higher percentage of intermediate-density lipoprotein (IDL) compared to controls (p=0.03 and p=0.01, respectively). Mean LDL size was lower in GHU compared to GHS (p=0.04). Percentage of intermediate HDL was lower in GHU and GHS compared to controls (p<0.001 and p<0.01, respectively). GHU demonstrated higher percentage of small HDL than controls (p<0.001). Overall, log10IGF-1 correlated positively with the percentage of large HDL (r=0.27; p=0.04) and intermediate HDL (r=0.38; p<0.01) and negatively with the percentage of small HDL (r=-0.46; p<0.01). Log10IGF-1 was the best predictor of small HDL (standardized β=-0.46; p<0.001) in overall subjects. In the GH-withdrawal study, the amount of HDL-6 increased with GH-withdrawal (p=0.03) and the percentage of IDL increased with reinstitution (p=0.05).ConclusionDespite no changes in standard lipid parameters, considerable alterations of lipoprotein subfractions were revealed in GH-deficient adults indicating that lipoprotein subfraction analysis may allow for a more precise cardiovascular risk assessment in AGHD. Associations between HDL subfractions and Log10IGF-1 demonstrate a novel insight into the role of GH in lipid metabolism.